PENGARUH CORPORATE GOVERNANCE TERHADAP DISCRETIONARY ACCRUALS PADA EMITEN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA - Makhdalena Makhdalena (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
In the late 2000s, the bankruptcy of giant corporations was due to accounting manipulation or called as discretionary accruals, has made accounting experts increasing attention to corporate governance that consist of (1) board of directors and (2) audit committee. This study purposes to obtain clarity empirical from the influence of its corporate governance to discretionary accruals. The population of this research is the banking sector companies listed on the Indonesia Stock Exchange as many as 31 companies and has been scrutinized. Mean while, the collection of data method use secondary data which obtained through each company’s annual report and whereas the data anlysis method uses path analysis with SPSS. As a reseach result, this study found influences of corporate governance, that are (1) board of directors and (2) audit committee on discretionary accruals either simultaneously or partially in the banking sector companies listed on the Indonesia Stock Exchange has proven to be exist and working effectively